LEARNERS’ PERCEPTIONS ON DIFFERENTIATED LEARNING IMPLEMENTATION IN WRITING CLASS: A STUDY IN A PRIMARY SCHOOL - Pratama, Yogi Atma; Fauzan, Akhmad; Asi, Natalina (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2023)
This research investigates sixth grade of elementary school students’ perceptions after learning writing descriptive text with Differentiated Instruction (DI). The current research employs survey research with questionnaire as the instrument. There are four key dimensions assessed from the questionnaire: the effectiveness of DI, supports from the teacher, ease of understanding, and students’ learning motivation. The findings reveal that DI significantly improved students' writing by simplifying complex tasks into manageable steps and making the learning process more engaging. Students appreciate the clear guidance and support from their teacher, which increased their confidence and comfort. DI also tailored instruction to individual needs, facilitating better comprehension and enjoyment of writing. The research concludes that DI effectively enhances students’ writing skills and suggests that future research should explore the long-term impacts of DI, integrate diverse assessment tools, and examine the role of teacher training in optimizing DI implementation.